Tunable 2D binary colloidal alloys for soft nanotemplating. Issue 47 (28th November 2018) - Fernández-Rodríguez, Miguel Ángel; Elnathan, Roey; Ditcovski, Ran; Grillo, Fabio; Conley, Gaurasundar Marc; Timpu, Flavia; Rauh, Astrid; Geisel, Karen; Ellenbogen, Tal; Grange, Rachel; Scheffold, Frank; Karg, Matthias; et al.
Abstract : 2D binary colloidal alloys obtained by sequential depositions of microgel monolayers used to fabricate vertically aligned nanowires by soft nanotemplating. Abstract : The realization of non-close-packed nanoscale patterns with multiple feature sizes and length scales via colloidal self-assembly is a highly challenging task. We demonstrate here the creation of a variety of tunable particle arrays by harnessing the sequential self-assembly and deposition of two differently sized microgel particles at the fluid–fluid interface. The two-step process is essential to achieve a library of 2D binary colloidal alloys, which are kinetically inaccessible by direct co-assembly. These versatile binary patterns can be exploited for a range of end-uses. Here we show that they can for instance be transferred to silicon substrates, where they act as masks for the metal-assisted chemical etching of binary arrays of vertically aligned silicon nanowires (VA-SiNWs) with fine geometrical control. In particular, continuous binary gradients in both NW spacing and height can be achieved. Notably, these binary VA-SiNW platforms exhibit interesting anti-reflective properties in the visible range, in agreement with simulations. The proposed strategy can also be used for the precise placement of metallic nanoparticles in non-close-packed arrays. Sequential depositions of soft particles enable therefore the exploration of complex binary patterns, e.g. for the future development of substrates for biointerfaces, catalysis and controlled wetting.